Review of In Vitro Flowering Method for Tomato (Solanum Lycopersicum L.) - Siska Citra Dewi; Vincentius Riandaru Prasetyo; Johan Sukweenadhi; Fenny Irawati; Wina Dian Savitri (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Tomatoes are one of the most popular vegetable plants globally because of the many benefts that can be obtained from tomatoes. However, its availability is still insuffcient for market demand. Therefore, researchers began to develop tissue culture methods to cope with market demand. Although there have been several studies on tomato ﬂowering in vitro, information about this method is minimal and needs further development. In vitro ﬂowering is a technique in tissue culture for ﬂowering plants in vitro. One of the benefts is cultivating plants in a relatively short time under controlled conditions to prevent disease transmission between plants. Therefore, we conducted a literature study to compare the results of these studies to know an eﬀective and efcient method of factors that increase the in vitro ﬂowering plants of tomatoes. In vitro ﬂowering methods generally focus on ﬂowering media, especially cytokinin types such as 6-Benzylaminopurine (BAP) and kinetin, and the concentration of those hormones, also light intensity used to induce ﬂowering of tomato plants. Factors that aﬀect in vitro ﬂowering of tomato plants are tomato plant varieties, hormones, and light intensity.